Solid Organ Transplantation in the Era of COVID-19 - Schuurmans, Macé M.; Hage, René (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes the coronavirus disease 2019 (COVID-19), posing a new challenge to the medical care of solid organ transplant (SOT) recipients. Due to the relatively small number of studies in SOT recipients suffering from COVID-19, the natural course of the SARS-CoV-2 infection, optimal treatment strategies including modification of immunosuppressive therapy and the prognosis in COVID-19 in these patients is incompletely understood. The current Special Issue aimed to fill some of the knowledge gaps and highlight some recent advances in the management of SOT patients during the pandemic. The call for manuscripts had been addressed to healthcare professionals involved in SOT patient care. We welcomed comprehensive reviews, original studies, interesting case series or case reports and commentaries relating to this topic.